Synthesis of amine-loaded styrene–divinylbenzene copolymers for carbon dioxide capture - Nande, Smita S.; Garnaik, Baijayantimala (ACS Engineering Au, 2025)
Carbon dioxide capture by various tertiary amines and quaternary bulky ammonium salts loaded in cross-link hybrid polymer (styrene–divinylbenzene copolymer) was explored. These polymeric materials were prepared by suspension polymerization in one pot using monomers like styrene and divinylbenzene in the presence of various amines to obtain uniform spherical beads. The homopolymer was separated from the cross-link hybrid product by Soxhlet extraction. The synthetic strategy is cost-effective and user-friendly, can be easily scaled up for production, and confirms better mechanical strength. The amine-loaded microporous polymeric spheres displayed a microsphere size of 5.2 nm with a high surface area of ∼25–310 m2 g–1. These hydrophobic polymeric spherical beads were thermally stable up to 200 °C. The quaternary ammonium group salt (bulky)-loaded beads presented high carbon dioxide uptake (up to ∼16.4 wt % at 273 K /1.0 bar) due to the presence of lone pair electrons of the heteroatom, which might improve the interaction between the polymeric matrices and CO2 molecules through local-dipole/quadruple interactions. In the case of tertiary amines, a high uptake of carbon dioxide (up to ∼15.2 wt % at 273 K /1.0 bar) was achieved, which is attributed to the formation of bicarbonate, as there may be the possibility of the presence of little moisture in the system, which facilitates the interaction. These hybrid polymeric materials exhibited a better storage capacity of CO2.